SBRT for bridging and downstaging HCC before transplant - Zhihao Li; Michael Yan; Marco P.A.W. Claasen; Luckshi Rajendran; Christian T.J. Magyar; Saheli Saha; Cameron Lee; Nazia Selzner; Elmar Jaeckel; Anand Ghanekar; Mark Cattral; Blayne A. Sayed; et al. (JHEP Reports, 2025)
Background & Aims: Stereotactic body radiotherapy (SBRT) has emerged as a bridging/downstaging therapy for patients with hepatocellular carcinoma (HCC) awaiting liver transplantation (LT). This study evaluates the safety and outcomes of the use of SBRT in such patients. Methods: A retrospective review was conducted from 2004 to 2019 on 88 adult patients with HCC receiving SBRT as bridging/downstaging therapy. Endpoints, included treatment-related toxicities, liver function decline, and LT probability post SBRT, were analyzed using competing risk analysis. Results: SBRT was used for bridging in 58 (66%) patients and downstaging in 30 (34%). Most patients had compensated liver function pre-SBRT and were treated with a median SBRT dose of 36 Gy in six fractions. Toxicities were mild (58% grade 1, 2% grade 2, and no grade 3 toxicities). Of the patients, 23% experienced a decline in liver function within 6 months post SBRT. The probability of LT post SBRT was 30% at 6 months, 61% at 1 year, and 73% at 2 years. Key predictors of LT post SBRT included model for end-stage liver disease (MELD) score, alpha-fetoprotein (AFP) level, and number and total tumor volume of HCC lesions. Overall, 61 (69%) patients underwent LT at a median of 6.3 months (IQR: 3.1–10.0) post SBRT, with major complications reported in 26% and an in-hospital mortality of 3%. Overall and recurrence-free survival at 1, 3, and 5 years post transplant were 88%, 83%, and 83% and 83%, 75%, 73%, respectively. The cumulative incidence of recurrence was significantly higher in the downstaging group compared with the bridging group (15%, 23%, and 32% vs. 7%, 15%, and 17% at 1, 3, and 5 years, respectively). Explant pathology revealed a 25% complete pathological response rate (bridging, 30%; downstaging, 12%). Conclusions: Our results showed that SBRT is a safe and effective bridging therapy for HCC. However, its role in downstaging is limited by lower response rates and higher recurrence, emphasizing the importance of patient selection. Impact and implications: SBRT is an emerging therapy for patients with HCC awaiting LT, with limited data available on its safety and efficacy. Our study provides crucial insights for physicians and researchers, demonstrating that SBRT is a safe and effective option for bridging patients with HCC to transplantation. These findings are important for optimizing treatment strategies and providing patients with additional therapeutic options while awaiting transplantation. However, the lower response rates and higher recurrence in the downstaging group highlight the need for further research to improve patient selection and tailor treatments for optimal outcomes.